2010
DOI: 10.3928/00989134-20100601-01
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Strategies for Atypical Presentation of Illness in Older Adults

Abstract: Atypical presentation of illness is a phenomenon where "seeing is believing." Expert geriatric nurses and clinicians know all too well the early signs and symptoms of this phenomenon, which frequently masquerades bacterial infections, pain, acute myocardial infarction, heart failure, or other serious medical ailments in older adults. Students, however, as novices to clinical practice, require interactive learning approaches to reflect on the patient's illness presentations, help with developing the necessary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Challenges to the detection of Infection in NH residents and altered physiology Signs of infection, such as fever in response to a bacterial infection, may be absent or altered, atypically presenting, aging structural and functional changes in the lung result in increased risk for pneumonia (Esme et al, 2019;Gray-Miceli et al, 2012;Meyer, 2005). Experts have found a dysregulation of the immune and inflammatory systems, most of which is associated with changes in T cell-mediated immunity, contributing to increase incidence of infectious diseases (Meydani, 2010).…”
Section: Resident Characteristics: Demographymentioning
confidence: 99%
See 3 more Smart Citations
“…Challenges to the detection of Infection in NH residents and altered physiology Signs of infection, such as fever in response to a bacterial infection, may be absent or altered, atypically presenting, aging structural and functional changes in the lung result in increased risk for pneumonia (Esme et al, 2019;Gray-Miceli et al, 2012;Meyer, 2005). Experts have found a dysregulation of the immune and inflammatory systems, most of which is associated with changes in T cell-mediated immunity, contributing to increase incidence of infectious diseases (Meydani, 2010).…”
Section: Resident Characteristics: Demographymentioning
confidence: 99%
“…physiological changes cause atypical presentation of illness (Esme et al, 2019;Gray-Miceli et al, 2012; refer to Table 1) making infections difficult to detect. A dysregulation of the immune and inflammatory systems also increases incidence of infectious diseases (Meydani, 2010;refer to (Bruggencate et al, 2018;McMaster Optimal Aging Portal, 2018).…”
Section: Resident Characteristics: Demographymentioning
confidence: 99%
See 2 more Smart Citations
“…Butter et al [ 27 ] have demonstrated transfer of skills and knowledge learnt through simulation training to the clinical environment. Learners having undergone simulation training accurately assessed 93.8% of simulated heart sounds ( P <.001) compared with 73.9% accuracy among untrained students [ 28 ]. The authors subsequently advocate for simulation-based mastery learning programs, contending that they are a practice and feasible modality, allowing sufficient time for practice and compliant with competency-based accreditation requirements [ 28 ].…”
Section: Discussionmentioning
confidence: 99%